2018
DOI: 10.1016/j.ins.2017.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Sparse representation based stereoscopic image quality assessment accounting for perceptual cognitive process

Abstract: In this paper, we propose a sparse representation based Reduced-Reference Image Quality Assessment (RR-IQA) index for stereoscopic images from the following two perspectives: 1) Human visual system (HVS) always tries to infer the meaningful information and reduces uncertainty from the visual stimuli, and the entropy of primitive (EoP) can well describe this visual cognitive progress when perceiving natural images. 2) Ocular dominance (also known as binocularity) which represents the interaction between two eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Thus, we obtain the gradient-related information of the cyclopean signal to get the binocular features. The difference signal is given by subtracting the right image from the left image, which has been proved that the difference information can well explain disparity perception in SIQA area [15], [57]. Works [58], [69] revealed that the difference signal is sensitive to the disparity and carries information critical for stereo perception.…”
Section: ) Binocular Perceptionmentioning
confidence: 99%
“…Thus, we obtain the gradient-related information of the cyclopean signal to get the binocular features. The difference signal is given by subtracting the right image from the left image, which has been proved that the difference information can well explain disparity perception in SIQA area [15], [57]. Works [58], [69] revealed that the difference signal is sensitive to the disparity and carries information critical for stereo perception.…”
Section: ) Binocular Perceptionmentioning
confidence: 99%
“… Yang et al (2018) proposed a RR-SIQA method based on sparse coding. Wan, Gu & Zhao (2019) proposed a RR-SIQA method that uses sparse representation and natural scene statistics to simulate the brain's visual perception.…”
Section: Introductionmentioning
confidence: 99%
“…With advancements in mathematics, sparse representation methods span a wide variety of applications, especially in the field of image processing, such as image segmentation [11], image denoising [12], visual tracking [13], and image super-resolution [14], etc. Meanwhile, sparse representation also shows great potential in dealing with the IQA issues [15][16][17]. Almost all existing sparse representation-based IQA methods follow a three-stage framework: dictionary learning (DL), qualityaware feature extraction, and regression model learning from subjective opinions.…”
Section: Introductionmentioning
confidence: 99%